Exploring the Interface of Skin‐Layered Titanium Fibers for Electrochemical Water Splitting. Issue 8 (5th January 2021) - Liu, Chang; Shviro, Meital; Gago, Aldo S.; Zaccarine, Sarah F.; Bender, Guido; Gazdzicki, Pawel; Morawietz, Tobias; Biswas, Indro; Rasinski, Marcin; Everwand, Andreas; Schierholz, Roland; Pfeilsticker, Jason; et al.
Abstract: Water electrolysis is the key to a decarbonized energy system, as it enables the conversion and storage of renewably generated intermittent electricity in the form of hydrogen. However, reliability challenges arising from titanium‐based porous transport layers (PTLs) have hitherto restricted the deployment of next‐generation water‐splitting devices. Here, it is shown for the first time how PTLs can be adapted so that their interface remains well protected and resistant to corrosion across ≈4000 h under real electrolysis conditions. It is also demonstrated that the malfunctioning of unprotected PTLs is a result triggered by additional fatal degradation mechanisms over the anodic catalyst layer beyond the impacts expected from iridium oxide stability. Now, superior durability and efficiency in water electrolyzers can be achieved over extended periods of operation with less‐expensive PTLs with proper protection, which can be explained by the detailed reconstruction of the interface between the different elements, materials, layers, and components presented in this work. Abstract : In this work, a very simple and scalable method is used to protect the titanium porous transport layers (PTLs) from passivation by sputtering very thin layers of Ir or Pt onto PTLs. 4000 h stable durability profiles are achieved when PTLs are coated with only 0.1 mg cm −2 of Pt or Ir. The results of this work show how the interface of a well‐protected titanium fiber behaves against passivation after long‐term operation under real electrolysis conditions.